2006
DOI: 10.1177/7010.2006.00300
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy Findings and Clinical Effects of Montelukast Sodium in a Case With Sjögren-Larsson Syndrome

Abstract: Sjögren-Larsson syndrome is a rare hereditary metabolic disorder characterized by congenital ichthyosis, mental retardation, and spastic diplegia or tetraplegia. This genetic disease is caused by fatty acid aldehyde dehydrogenase deficiency, leading to an accumulation of long-chain alcohols. The role of enzyme in the degradation of leukotrienes paved the way to the development of a new therapeutic strategy for Sjögren-Larsson syndrome, leukotriene antagonists. We describe a 3-year-old boy with Sjögren-Larsson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…El hallazgo de un pico de lípidos en la ERM en este paciente podría ser explicado por el acúmulo de metabolitos grasos anormales en el parénqui-ma cerebral, dada la falla enzimática en el ciclo oxidativo de los ácidos grasos de cadena larga. [13][14][15] . El pico de láctico se observa en otras entidades metabólicas, como trastornos mitrocondriales, y en aquellas por depósitos de sustancias patológi-cas por disfunción mitocondrial.…”
Section: Discussionunclassified
“…El hallazgo de un pico de lípidos en la ERM en este paciente podría ser explicado por el acúmulo de metabolitos grasos anormales en el parénqui-ma cerebral, dada la falla enzimática en el ciclo oxidativo de los ácidos grasos de cadena larga. [13][14][15] . El pico de láctico se observa en otras entidades metabólicas, como trastornos mitrocondriales, y en aquellas por depósitos de sustancias patológi-cas por disfunción mitocondrial.…”
Section: Discussionunclassified
“…EEG showed a slow background activity, without other abnormalities in a study of 19 children, adolescents and adult patients (Willemsen et al 2001a). No peripheral and spinal sensory conduction disorders or motor conduction velocity abnormalities are commonly observed: in some patients however values outside the reference ranges can be recorded (Gordon 2007, Rizzo 2006 (Mano et al 1999;Miyanomae et al 1995;van Somburg et al 1999;Willemsen et al 2000Willemsen et al , 2001aWillemsen et al , 2004Pirgon et al 2006). MRI shows widespread periventricular low signal on T 1 -weighted images and high signal areas on T 2 -weighting, most prominent around the trigones, mild ventricular enlargement, diffuse brain atrophy and a mildly hypoplastic corpus cal- (Fig.…”
Section: Neurophysiologic Investigationmentioning
confidence: 94%
“…139,141 A sharp lipid peak is present on MRS of the cerebral white matter and basal ganglia which differs from that found in other white matter diseases. 141,142 It is believed to arise from the accumulation of long-chain fatty alcohols or aldehydes.…”
Section: Sjögren-larsson Syndromementioning
confidence: 99%
“…146 Beneficial effects have been described using the LTB 4 synthesis inhibitor Zileuton. 142,147 In vitro studies have shown that residual FALDH activity in patient fibroblasts can be induced with the hypolipidemic drug bezafibrate. 148 This finding raises the possibility that bezafibrate might be used to treat patients who have residual FALDH activity.…”
Section: Sjögren-larsson Syndromementioning
confidence: 99%